Jewish displaced persons in Italy 1943-1951 - Renzo, Chiara, 1988- author.
1 online resource.
Keywords: "This book focuses on the experiences of thousands of Jewish displaced persons who lived in refugee camps in Italy between the liberation of the southern region in 1943 and the early 1950s, waiting for their resettlement outside of Europe. It explores daily life in the refugee camps, and interaction with the multitude of international actors involved in the rescue, rehabilitation and resettlement of the Jewish peoples. Drawing on a wide array of sources, this book sheds light on the dilemmas people faced when reconstructing their lives when, as refugees, they were able to shape a vivid temporary community. Against the backdrop of the better-known events of clandestine emigration, the book explores the Jewish displaced persons' approach to Zionism, their cultural revival, the role of humanitarian organizations and the attitude of the Italian authorities"--